Differences in epidemiological features between ulcerative colitis and Crohn's disease: The early life-programmed versus late dysbiosis hypothesis. (June 2018) - Beaugerie, Laurent; Langholz, Ebbe; Nyboe-Andersen, Nynne; Pigneur, Bénédicte; Sokol, Harry; ,
Abstract: It is increasingly admitted that Crohn's disease and ulcerative colitis, the two entities of inflammatory bowel disease, are initiated and reactivated by environmental factors in genetically susceptible hosts, and result from aberrant immune response to specific intestinal microbes, in the context of altered composition of intestinal microbiota, called dysbiosis. We hypothesize that the role of the gut microbiota in Crohn's disease pathogenesis is linked to early-life abnormal crosstalk with the host immune system under construction. By contrast, in ulcerative colitis, the detrimental effect of intestinal dysbiosis could occur at any time of life, due to instant environment. This hypothesis could explain why the incidence of Crohn's disease raises many years later than that of ulcerative colitis in developing countries that adopt the Western lifestyle. This would also explain why many early-life events, such as caesarean section, increased hygiene and repeated antibiotic exposure, are risk factors for subsequent development of Crohn's disease, but not ulcerative colitis.